Pengaruh Konseling Kelompok Berbasis Experiential Learning terhadap Konsep Diri Mahasiswa - Sofah, Rahmi (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2021)
Self-concept is a person's view of himself, if someone has a positive view of himself, it will develop the nature of self-confidence and the ability to see himself positively. The purpose of this study was to determine the effect of experiential learning-based group counseling services on the self-concept of students of the Guidance and Counseling study program FKIP Unsri. The research subjects were taken by purposive sampling technique, based on the analysis of the results of the identification of needs, obtained 7 students who became research subjects. This study uses an experimental method with a One-Group Pre-test Post-test design. The data collection instrument used was a questionnaire. From the results of the research, the students' self-concept scores were 68.42 in the medium category, after the post-test results increased with a self-concept score of 112.42 in the high category. Based on the results of the t-test, it is obtained that it is greater than t-table at a significance level of 5% (3.56> 2.45. This indicates that there is a significant effect of Experiential Learning-based group counseling services on students' self-concepts.